Plant protein and vegetable oil‐based diets modulate gilthead seabream (Sparus aurata) muscle biochemical status and proteolytic enzymes at an early postmortem stage. (16th January 2014) - Matos, E.; Silva, T.S.; Colen, R.; Dinis, M.T.; Dias, J.
Abstract A 70 days feeding trial was carried out on juvenile gilthead seabream (Sparus aurata) (mean initial body weight: 362 ± 59 g) to evaluate whether the simultaneous replacement of fishmeal and fish oil by vegetable ingredients affected the muscle's proteolytic potential. Fish were fed either a fishmeal/fish oil diet, a fishmeal/vegetable oil diet, a plant protein/fish oil or a plant protein/vegetable oil diet. The use of dietary plant proteins resulted in lower sulphated glycosaminoglycans' content and lower glycogen phosphorylase activity in the muscle, while both plant proteins and vegetable oil increased muscle pH and reduced cathepsin B activity. Our results indicate that high replacement of fish meal and/or fish oil with plant ingredients has a significant impact on early postmortem metabolic processes and proteolytic potential of seabream muscle, especially when replacing both fish meal and fish oil.